Analisis Faktor-Faktor Motif terhadap Minat Berdagang di Pasar Tradisional (Studi Pada Pasar Pedan Klaten) - Nurlaili, Septiana (Universitas PGRI Yogyakarta, 2020)
The Objective of the study is to determine the motive factors, they are personality, skills and intentions of the interest in trading in Pedan traditional market of Klaten regency. Ther data were taken in the form of primary data obtained through questionnaires and respondents are traders of the Pedan Klaten Market. The Analytical method used consist of validity, reliability, multiple regression analysis, classic assumptions, t test and coeddicient of determination tests. From the results of the study it can be concluded that the results of the regression analysis obtained the following equation: Y= 6,508 + -0,042X1 + 0,356X2 + 0,507X3 +e. Based on the results of the t test personality does not have an influence on trading interest and then skills have a positive and significant effect on trading interest and intention has a positive and significant effect on trading interest. The most dominant variable in this study is skills.